Analisis waktu konversi pemeriksaan Bakteri Tahan Asam (BTA) positif pada penderita tuberkulosis paru di Rumah Sakit Umum Daerah (RSUD) Labuang Baji, Makassar - Anwar Sadaq; Nursin Abd Kadir; Benny Rusli (Intisari Sains Medis, 2020)
Background: Tuberculosis (TB) is a dangerous infectious infection and a global health problem. Conversion rate is the percentage of acid-resistant bacilli positive pulmonary tuberculosis patients who have converted to negatives smears since initial therapy. Besides, the conversion failure cases indicate the risk of TB transmission can still occur, which means the failure of TB treatment. This study aims to analyze the results of the conversion of smear microscopic (+) to smear microscopic (-) from pulmonary TB patients in Labuang Baji Hospital Makassar since conducting anti-tuberculosis drug therapy (DOTS). Method: The research design of the longitudinal approach is retrospective among 85 respondents. The study was conducted in January 2017-2018 at the Labuang Baji Hospital in Makassar. Samples were all Tuberculosis patients based on Microscopic smear and Fast Molecular Test results. Data were analyzed using SPSS version 17 for Windows.Result: The change of conversion time in the first month is 14 (16.5%), the second month is 36 (42.4%), the highest conversion results occurred in the third, fourth, fifth and sixth months, namely 73 (85.9%) on average 0.25 with P-value <0.005, as expected by an Indonesian Government program that the result of microscopic smear conversion in pulmonary TB patients is expected to reach a minimum of <80%. Patients with microscopic smear-positive results to Fast Molecular Test with high bacterial load risk failure conversion. Conclusion: conversion results at Labuang Baji Regional Public Hospital in Makassar based microscopic smear showed promising results as expected by the national target of 85,9%. A positive correlation between a microscopic smear and a Fast Molecular Test results in the success of the conversion.  Latar belakang: Tuberkulosis (TB) merupakan infeksi menular yang berbahaya dan  menjadi masalah kesehatan global. Angka konversi adalah persentase pasien TB paru BTA positif yang mengalami konversi menjadi BTA negatif sejak terapi awal. Sedangkan kasus gagal konversi menunjukkan risiko penularan TB masih dapat terjadi,yang menunjukan adanya ketidakberhasilan pengobatan TB. Penelitian ini bertujuan untuk menganalisis hasil konversi pemeriksaan BTA (+) menjadi BTA (-) penderita TB paru di RSUD Labuang Baji Makassar sejak terapi obat anti tuberkulosis (OAT).Metode: Desain penelitian pendekatan longitudinal bersifat retrospektif terhadap 85 responden. Penelitian dilakukan periode Januari 2017 – Januari 2108 di  RSUD Labuang Baji Makassar ,Sampel adalah semua pasien TB berdasarkan hasil BTA  mikroskopik dan TCM. Data dianalisis dengan SPSS versi 17 untuk Windows.Hasil: Perubahan lama konversi bulan pertama 14 (16,5%),bulan kedua 36 (42,4%), Hasil  konversi tertinggi terjadi dibulan ketiga, keempat, kelima, dan keenam  yaitu 73 (85.9%)  rerata 0,25 dengan P value < 0.005, sesuai yang diharapkan program pemerintah Indonesia bahwa hasil konversi BTA pada pasien TB paru diharapkan mencapai minimal <80%.  Pasien dengan hasil pemeriksaan BTA mikroskopik BTA positif terhadap TCM dengan bacterial load high memiliki resiko gagal konversi.Simpulan: Hasil konversi BTA di RSUD labuang baji Makassar menunjukan hasil yang baik sesuai yang diharapkan target nasional yaitu 85,9%. Terdapat korelasi mengenai derajat positifitas hasil TCM dan BTA mikroskopik  terhadap keberhasilan konversi pasien TB paru.